Living laboratory of regional potential for social studies learning to enhance students' collaboration and communication - Pristine Adi, Depict; Maryani, Enok; Ruhimat, Mamat; Komalasari, Kokom (Program Pascasarjana Universitas Negeri Yogyakarta, 2025)
21st-century education requires collaboration and communication skills as students' core competencies, but social studies learning at the junior high school level still tends to be textual and lacks local potential. This study uses a qualitative approach with a case study design at SMPN 1 Wuluhan, Jember Regency, involving social studies teachers and grade VIII students through participatory observation, semi-structured interviews, documentation, and questionnaires to 60 students, with data analysis of Miles, Huberman, and Saldaña models validated through triangulation methods and member checking. The results show that the potential of the Wuluhan area—such as Papuma Beach, Watangan Hill, Reog craft center, and Charcoal Factory—provides an authentic learning experience that strengthens the connection of social studies materials with local reality; 91.6% of students consider field activities to be more meaningful than classroom learning. Collaboration skills are improving well, particularly in respecting friends' opinions (85%). In comparison, communication skills improve in listening (83%), although the courage to ask questions is still low (72%). Interviews and observations confirm that field learning encourages active participation, confidence, and more natural social interaction. The main supporting factors for implementation are the diversity of local potential, student enthusiasm, and community support, while obstacles include weather, transportation costs, and time constraints. Overall, this study confirms that the living laboratory is efficacious in improving the collaboration and communication skills of junior high school students through participatory contextual learning, while strengthening cultural identity and learning motivation, with the note that successful implementation requires strategies to mitigate technical constraints and synergistic support between schools, communities, and local governments.